2004
DOI: 10.1111/j.1540-6210.2004.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Perspectives on the Practice of Leadership

Abstract: Public administrators need not only practical and intellectual permission to exercise leadership, but also a practical and intellectual understanding of what leadership actually is. Much has emerged in the public administration literature and practice about the need for and legitimacy of public managers exerting leadership in their work, complementing the traditional functions of organizational management and policy implementation. Calling on the experiences and ideas of practitioners, this article offers an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 16 publications
0
63
0
8
Order By: Relevance
“…In fact, it has been observed that there are as many definitions of leadership as there are people trying to define it (Bass, 1990). Thus, in the absence of agreement about what leadership is and who a leader is understood to be, those who practice leadership may do so from very different mindsets (Fairholm, 2004).…”
Section: The Multiplicity Of Meaningmentioning
confidence: 99%
“…In fact, it has been observed that there are as many definitions of leadership as there are people trying to define it (Bass, 1990). Thus, in the absence of agreement about what leadership is and who a leader is understood to be, those who practice leadership may do so from very different mindsets (Fairholm, 2004).…”
Section: The Multiplicity Of Meaningmentioning
confidence: 99%
“…A possible mutation of it is the efficiency meme which was heavily drawn on by the scientific management movement of the early part of the 20 th century, and still has relevance for many managers today [38]. A version of the efficiency meme could be Gulick's [39] POSDCORB (planning, organizing, staffing, directing, coordinating, reporting, and budgeting) meme that adhered to Fayol's [40] tenets or principles of organisation and management (forecast and plan -prevoyance, organise, command, co-ordinate, control), and Taylor's [41] framework for organisation (clear delineation of authority, responsibility, separation of planning from operations, incentive schemes for workers, management by exception and task based specialisation).…”
Section: Division Of Labourmentioning
confidence: 99%
“…Given this private sector focus, it is surprising, therefore, that a critical examination of government leadership policies has been slow to follow. Several scholars have called for an assessment of the influence of public sector context on the efficacy of different leadership approaches (Fairholm, 2004;Javidan & Waldman, 2003;Van Wart, 2003).…”
Section: Introductionmentioning
confidence: 99%